2023
DOI: 10.3389/fimmu.2023.1269391
|View full text |Cite
|
Sign up to set email alerts
|

Targeting intracellular galectins for cancer treatment

Rita Nehmé,
Yves St-Pierre

Abstract: Although considerable attention has been paid to the role of extracellular galectins in modulating, positively or negatively, tumor growth and metastasis, we have witnessed a growing interest in the role of intracellular galectins in response to their environment. This is not surprising as many galectins preferentially exist in cytosolic and nuclear compartments, which is consistent with the fact that they are exported outside the cells via a yet undefined non-classical mechanism. This review summarizes our mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…For both proteins, the MEAN-nMS assay detected binding to all six gangliosides possessing a terminal or otherwise accessible Gal residue. Of these, only GM1 has previously been shown to be a ligand. That no binding was detected for GM2 and GD2, which lack terminal Gal, establishes that anchoring the GBPs to the ND does not lead to false positives (nonspecific binding). These results are in sharp contrast to the complete absence of detectable binding in the case of unlabeled GAL-7 and the much lower levels of specific binding and false negatives measured for unlabeled GAL-3C.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For both proteins, the MEAN-nMS assay detected binding to all six gangliosides possessing a terminal or otherwise accessible Gal residue. Of these, only GM1 has previously been shown to be a ligand. That no binding was detected for GM2 and GD2, which lack terminal Gal, establishes that anchoring the GBPs to the ND does not lead to false positives (nonspecific binding). These results are in sharp contrast to the complete absence of detectable binding in the case of unlabeled GAL-7 and the much lower levels of specific binding and false negatives measured for unlabeled GAL-3C.…”
Section: Resultsmentioning
confidence: 98%
“…Galectins, which represent an important class of immune lectins, recognize glycans possessing terminal β-galactose (Gal) residues . The GSL specificities of human galectins are not well characterized, although GAL-3C (and GAL-3) and GAL-7 are known to recognize neutral GSLs, including lacto- and neolacto-GSLs. Gangliosides are also suggested to bind and there is evidence of GAL-3 and GAL-7 interactions with GM1 on model and cell membranes. As the ganglioside binding properties of GAL-3C and GAL-7 have not been comprehensively established, the MEAN-nMS data were assessed by comparison to the affinities (Table S1) of the corresponding ganglioside oligosaccharides measured in the present study (Figures S3 and S4) and previously reported data (for GM3 os ) . According to the affinity data, neither GM2 os nor GD2 os (both of which lack terminal Gal) is recognized by GAL-3C or GAL-7, in line with expectations.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that the extracellular galectins, a family of multivalent lectins, decode information stored in N-glycan chains attached to FGFRs on the cell surface and secreted FGFs to fine-tune FGF/FGFR signaling [ 31 – 37 ]. Galectins are also found inside the cell, where they interact with several proteins binding their proteinaceous cores, participating among the others in protein trafficking, signal transduction and apoptosis [ 38 ]. In light of the significant role of galectins in N-glycan-dependent FGF/FGFR signaling and in the search for regulators of nuclear FGF12, we tested the interplay between intracellular FGF12 and selected members of the galectin family.…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-1 (Gal-1) is an evolutionarily conserved β-galactoside-binding protein found intracellularly and extracellularly. It is synthesized as a cytosolic protein and can function in intracellular spaces [4,5]. However, it is secreted by nonclassical pathways, such as necroptosis [6] or presently undetermined pathways, and functions extracellularly in various biological phenomena, such as immunity, cancer, and differentiation [4,7].…”
Section: Introductionmentioning
confidence: 99%